Perlindungan Kebebasan Berpendapat Pada Pemilihan Umum di Kabupaten Minahasa Selatan - Siar, Lendy; Lambonan, Marthin Luther; Mamengko, Rudolf Sam (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Protecting freedom of expression is a critical component in ensuring that the democratic process goes well, particularly during general elections such as the presidential election, DPR, DPRD, and DPD in North Minahasa Regency. This study will look at how the government safeguards free expression during the electoral process. In a democratic system, freedom of expression serves as the primary foundation for people to express their political beliefs, actively participate in public debates, and make informed judgments. However, political pressure, abuse of authority, and the propagation of disinformation frequently make it difficult to execute this safeguard. This study examines government policies, applicable laws, and steps taken to safeguard freedom of expression, while ensuring a fair and transparent election process. In addition, this study highlights the role of election supervisory institutions, law enforcement officers, and the media in safeguarding this freedom. The results of the study show that although there have been various policies to protect freedom of expression, there are still obstacles in their implementation, especially related to control over press freedom and freedom of expression on social media. Therefore, it is necessary to strengthen policies and more effective oversight mechanisms to ensure that every citizen can express their opinions freely and without intimidation in every stage of the general election in North Minahasa Regency.